Low-paid EU migrant workers : the house, the street, the town - Barnard, Catherine; Costello, Fiona; Fraser Butlin (Bristol University Press, 2024)
No detailed description available for ""Low-Paid EU Migrant Workers""
Keywords: Migrant labor -- Great Britain.; Migrant labor -- Great Britain -- Social conditions.; Immigrants -- Employment -- Great Britain.; Travailleurs migrants -- Grande-Bretagne.; Travailleurs migrants -- Grande-Bretagne -- Conditions sociales.; LAW -- Emigration & Immigration.